The Relationship between Intelligence quotient and Mastery of Biodiversity Material Using E-Modules - Oktaviani, Listiawati; Adisyahputra; Isfaeni, Hanum (Biosfer: Jurnal Pendidikan Biologi, 2024)
E-modules can facilitate student understanding of complex biological concepts, including biodiversity, but their effectiveness also depends on individual student abilities. One significant factor influencing this success is the students' intelligence quotient, which affects how they process and comprehend complex information. This research aims to determine the relationship between intelligence quotient with mastery of biodiversity material using e-modules. The method used in this research is a quantitative descriptive method with correlation studies. The sample was taken from as many as 177 students from SMAN in Tangerang City was collected using multistage random sampling technique. To assess these skills, a test instrument in the form of multiple-choice questions is used. The prerequisite test shows that the data is normally distributed, the data is homogeneous, the data is linear, the data is free from symptoms of heteroscedasticity, the data is not multicollinearity, and the data is free from symptoms of autocorrelation. Through testing the hypothesis, the equation Ŷ = 41.268 + 0.580X1 is obtained. The correlation coefficient obtained was 0.881, which means there is a very strong relationship. . Based on this research, it can be concluded that there is a positive relationship between intelligence quotient, reading comprehension ability, and mastery of biodiversity material using e-modules.